„Stworzenie człowieka” i typy komunikowania. Studium hermeneutyczne - Paradowski, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The author of the paper highlights that McQuail’s typology of communication, which is most commonly applied in Polish science, and quoted as a whole by Tomasz Goban-Klas, among others, refers to levels of communication discerned by means of a quantitative criterion. In the author’s opinion, however, a type cannot be solely by quantitative differences. Therefore, he suggests that two types of communicative relations be directly referred to: obedience and covenant, which can in his opinion, alread btered in the Old Testament. He identifies two fundamental types of communication on this basis: an advanced type, where the sender is simultaneously a recipient, and the recipient is a sender; and a reduced type where the sender is only a sender, and the recipient only a recipient, which is a result of a significant disproportion of power between the parties.